Inter-rater reliability of certain parameters of basketball jump shot - Erculj, F.; Markovic, M.; Leskošek, B.; Supej, M. (Kinesiologia Slovenica, 2021)
The ability to visually perceive the movement of athletes or objects they handle is an important skill in sport training practice. The aim of this study was to establish whether basketball coaches are capable of uniformly (congruently) evaluating the release time, release angle, ball rotation and overall correctness of a jump shot by observing it with the naked eye. The study included a sample of 13 coaches (six with more and seven with less experience) whose task was to evaluate basketball jump shots made by young basketball players aged 15.1 (± 0.75) years on average from a distance of 4.5 m. The values of Pearson`s correlation coefficients and multiple correlation coefficients (generally above 0.7) as well as Cronbach`s alpha coefficients (above 0.9) and Kendall`s W coefficients of concordance (mostly below 0.1) show a high level of uniformity and congruence in the evaluations of the quality (correctness) of a shots as a whole and also individual shot parameters. Quite a lower level of uniformity and congruence can be established in the evaluations of the consistency of individual parameters. This applies to both groups of more experienced and less experienced coaches (raters). The results allowed an assessment that the levels of reliability of the evaluation of the group of at least six raters are appropriate for scientific research. Given the low values of the ICC (Inter Class Correlations), only equalling about 0.6, we can say that only one rater did not meet the scientific evaluation criteria.